Using Transformation Technique to Improve Writing Skill of Short Story - Hani Novianti & Daud Pamungkas (Universitas Suryakanca, 2018)
This article discusses the learning of writing short stories with transformational techniques, transforming Sundanese Cianjuran songs into a short story. The study was applied to students of class IX at SMP Bina Utama in 2017-2018. The research method used is the experimental method (Pre Experimental Desaign). The sample used is the IXE class and it is chosen based on certain considerations. The instruments used are observation and tests. The results showed that the results of learning to write short stories before using text transformation techniques (pretest) were classified as low, with an average pretest score of 50.68, while using the text transformation technique (posttest) the results were in the medium category, with the average posttest result was 65,45. Then, after being compared with the t-test, the significance value of the data before and after treatment is 0,000, which means the significance value is 0,000 <0,05, then H0 is rejected. From the results of the significance test, it can be said that the treatment (learning technique) that has been applied in this study is the text transformation technique in writing short stories successfully increasing students' short story writing skills.Keywords: writing, short stories, transformation, tembang Sunda